2018
DOI: 10.1002/ijc.31333
|View full text |Cite
|
Sign up to set email alerts
|

Serum insulin‐like growth factor (IGF)‐I and IGF binding protein‐3 in relation to terminal duct lobular unit involution of the normal breast in Caucasian and African American women: The Susan G. Komen Tissue Bank

Abstract: Lesser degrees of terminal duct lobular unit (TDLU) involution, as reflected by higher numbers of TDLUs and acini/TDLU, are associated with elevated breast cancer risk. In rodent models, the insulin-like growth factor (IGF) system regulates involution of the mammary gland. We examined associations of circulating IGF measures with TDLU involution in normal breast tissues among women without precancerous lesions. Among 715 Caucasian and 283 African American (AA) women who donated normal breast tissue samples to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Biologically, IGF-1 and IGFBP3 levels appear to drive only TDLU counts and do not otherwise impact other TDLU measures such as span or acini counts per TDLU [7, 8], consistent with our inability to detect either span or acini score associations with HDP and/or rs2016347 genotypes (results not provided). Across epidemiologic studies, HDP by itself only marginally reduces later-life breast cancer risk; but, as seen here and in two prior studies [1921], inheritance of the functionally blunted rs2016347 TT genotype appears to combine with the biological impact of HDP to reduce mammary gland TDLUs, mammographic density, and later-life breast cancer incidence.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Biologically, IGF-1 and IGFBP3 levels appear to drive only TDLU counts and do not otherwise impact other TDLU measures such as span or acini counts per TDLU [7, 8], consistent with our inability to detect either span or acini score associations with HDP and/or rs2016347 genotypes (results not provided). Across epidemiologic studies, HDP by itself only marginally reduces later-life breast cancer risk; but, as seen here and in two prior studies [1921], inheritance of the functionally blunted rs2016347 TT genotype appears to combine with the biological impact of HDP to reduce mammary gland TDLUs, mammographic density, and later-life breast cancer incidence.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, longitudinal data have shown that women whose breast tissue demonstrates slower involution over time also have increased breast cancer risk [5]. The insulin-like growth factor (IGF) pathway has been implicated in playing a role in the involution process, and decreased levels of IGF-1 and increased levels of one of its binding proteins, IGFBP3, have been associated with lower TDLU counts [68].…”
Section: Introductionmentioning
confidence: 99%
“…Increases in BMI have temporally paralleled early onset of breast development and menarche, but the interval between these events has widened, which is speculated as contributory to elevated BC risk [ 35 ]. Previous studies in KTB reported that African American women had higher circulating levels of insulin-like growth factor binding protein-3 (IGFBP-3) than white women, and that among postmenopausal women of both races, IGFBP-3 was inversely related to TDLU counts [ 36 ]. We propose that future studies of normal breast tissues may provide insights into why rates of early onset BCs differ by race.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1R overexpression is associated with decreased breast cancer survival, increases in recurrence, and treatment resistance to radiation and Herceptin, which are both used to treat brain metastases [ 25 , 26 , 27 ]. In addition, IGF-1 and IGF binding protein 3 are also associated with breast cancer risk, progression, recurrence, and the probability of survival in African American women [ 28 , 29 ]. Therapies that can be added to radiation that increase local control and metastases would be optimal.…”
Section: Breast Cancer and Radiation Response In The African American Populationmentioning
confidence: 99%